2018
DOI: 10.5194/aab-61-305-2018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leptin genetic polymorphism on lameness prevalence in Tunisian Holstein cows

Abstract: Abstract. Lameness is the third most important infection affecting dairy cattle in modern stabling barns. Environmental (food, stables and injuries) and genetic factors are responsible for this pathology. This study aims to investigate the screening of leptin genetic polymorphism and its effect on lameness prevalence. DNA was extracted from 412 blood samples from Holstein cows (lame and healthy). Genotyping was performed by the PCR-RFLP using the Sau3AI restriction enzyme. Prevalence of parity, calving season,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Considering other similar studies, the allele frequencies reported in the studies by Pomp et al (1997), Rasor et al (2002), Javanmard et al (2004), Leifers et al (2002, Javanmard et al (2005), Javanmard et al (2010), Kulig et al (2010), Öztabak et al (2010), Aytekin, (2011), Al-Janabi et al (2018), Ferchichi et al (2018, Maletic et al (2019), Kiyici et al (2019;Fernandes et al (2020) were similar to the allele frequencies in our study. According to the Hardy-Weinberg genetic equilibrium test performed for both breeds, LEP/Sau3AI gene polymorphism was in equilibrium in the Brown Swiss breed (X 2 =2.44; P>0.05), while it was not in equilibrium in the Simmental breed (X 2 =4.67; P<0.05).…”
Section: Resultssupporting
confidence: 90%
“…Considering other similar studies, the allele frequencies reported in the studies by Pomp et al (1997), Rasor et al (2002), Javanmard et al (2004), Leifers et al (2002, Javanmard et al (2005), Javanmard et al (2010), Kulig et al (2010), Öztabak et al (2010), Aytekin, (2011), Al-Janabi et al (2018), Ferchichi et al (2018, Maletic et al (2019), Kiyici et al (2019;Fernandes et al (2020) were similar to the allele frequencies in our study. According to the Hardy-Weinberg genetic equilibrium test performed for both breeds, LEP/Sau3AI gene polymorphism was in equilibrium in the Brown Swiss breed (X 2 =2.44; P>0.05), while it was not in equilibrium in the Simmental breed (X 2 =4.67; P<0.05).…”
Section: Resultssupporting
confidence: 90%
“…Logistic regression was used to identify the explanatory facteurs, from there cited above, of fertility rate and conception rate (Ferchichi, Jemmali, Amiri, Ben Gara, & Rekik, 2018). These dependant variables were considered as binary response, and the 5% level of significance was considered.…”
Section: Methodsmentioning
confidence: 99%
“…In a study in Turkey, Guzel et al (2012) determined serum leptin levels in Brown Swiss (2.35±0.34 ng/ml), Holstein bulls (3.55±0.53 ng/ml), Avesi sheep (2.16±0.29 ng/ml), saanen (2.23±0.46 ng/ml) and hair goats (0.94±0.10ng/ml) by the radio immune assay (RIA) method. In the early 2000s, studies investigating leptin levels serologically were more common, but in the following years more genetic studies began to gain importance (Ferchichi et al, 2018;Kaplan, 2018;Abbas et al, 2019;Avondo et al, 2019;Das et al,2019;Ibrahim et al, 2020;Mahrous et al, 2020;Sedykh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%